Tracing Mobile DNAs: From Molecular to Population Scales - Fan, Wenwen; Wang, Ling; Chu, Jie; Li, Hui; Kim, Eun Yu; Cho, Jungnam (Frontiers in Plant Science, 2022)
Transposable elements (TEs, transposons) are mobile DNAs that are prevalent in most eukaryotic genomes. In plants, their mobility has vastly contributed to genetic diversity which is essential for adaptive changes and evolution of a species. Such mobile nature of transposon has been also actively exploited in plant science research by generating genetic mutants in non-model plant systems. On the other hand, transposon mobilization can bring about detrimental effects to host genomes and they are therefore mostly silenced by the epigenetic mechanisms. TEs have been studied as major silencing targets and acted a main feature in the remarkable growth of the plant epigenetics field. Despite the importance of transposon in plant biology and biotechnology, their mobilization and the underlying mechanisms are largely left unanswered. This is mainly because of the sequence repetitiveness of transposons, which makes their detection and analyses difficult and complicated. Recently, some attempts have been made to develop new experimental methods detecting active transposons and their mobilization behavior. These techniques reveal TE mobility in various levels, including the molecular, cellular, organismal and population scales. In this review, we will highlight the novel technical approaches in the study of mobile genetic elements and discuss how these techniques impacted on the advancement of transposon research and broadened our understanding of plant genome plasticity.